Adverse Events Following Primary and Secondary Immunisation with Whole-Cell Pertussis: A Systematic Review Protocol - Patterson, Jenna; Kagina, Benjamin M.; Gold, Michael; Muloiwa, Rudzani (BMJ open, 2017)
Pertussis is a contagious respiratory illness caused by the bacterium Bordetella pertussis. Two types of vaccines are currently available against the disease: whole-cell pertussis (wP) and acellular pertussis (aP). With the shift of high-income countries from wP to aP as a result of adverse events following immunisation (AEFI), an upsurge in reported cases of pertussis has been noticed. Owing to this, it is proposed to use wP as a prime and aP for boost vaccination strategy. However, a comparison of the AEFI with the first doses of wP and aP are not clearly documented. The primary outcomes of interest are AEFI with dose 1 of wP, subsequent doses of wP and dose 1 of aP. As a secondary outcome frequency of AEFI with wP will be compared with the AEFI of doses 2 and 3 of wP and dose 1 of aP. Electronic databases will be searched and two authors will screen the titles and abstracts of the output. Full texts will then be independently reviewed by the first author and two other authors. Qualifying studies will then be formally assessed for quality and risk of bias using a scoring tool. Following standardised data extraction, statistical analysis will be carried out using STATA. Where data are available, subgroup analyses will be performed. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines will be followed in reporting the findings of the systematic review and meta-analysis.
Keywords: Pertussis; AEFI; STATA; immunisation